Investigating the Teaching of Block Programming in High School - Perin, Ana Paula Juliana; Silva, Deivid Eive; Valentim, Natasha Malveira Costa (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context:Designing and developing Information Systems (IS) thro-ugh block programming can support the encouragement of 21st-Century skills such as problem-solving and logical reasoning, among other skills that are useful in the development of IS. Problem:High school students, in general, may have difficulty learning and using textual programming languages due to the programming language syntax complexity. Solution:Therefore, this paper presents a survey that sought to understand how and which block programming tools are being used to support the teaching and learning of programming in High School. IS Theory:This survey is part of the application of the first stage of Design Theory, which seeks to create a knowledge base about using block programming in High School. Method:The survey was carried out with 36 high school teachers. Data were collected and analyzed quantitatively, and qualitatively through the Grounded Theory method. Summary of Results:The findings indicate the teachers’ little knowledge about the block programming tools, few support materials and the difficulties of schools in incorporating the new Digital Information and Communication Technologies (DICTs). Contributions and Impact in the IS area:Identifying the difficulties of teachers and students in the use of block programming in high school can open ways to improve the development of IS by students, and consequently, the development of 21st-Century skills.